2011
DOI: 10.1089/ast.2010.0574
|View full text |Cite
|
Sign up to set email alerts
|

Sunspot Dynamics Are Reflected in Human Physiology and Pathophysiology

Abstract: Periodic episodes of increased sunspot activity (solar electromagnetic storms) occur with 10-11 and 5-6 year periodicities and may be associated with measurable biological events. We investigated whether this sunspot periodicity characterized the incidence of Pap smear-determined cervical epithelial histopathologies and human physiologic functions. From January 1983 through December 2003, monthly averages were obtained for solar flux and sunspot numbers; six infectious, premalignant and malignant changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
1
15
1
Order By: Relevance
“…In contradiction to some studies that have described the association of high solar activity and human health in the literature (Palmer et al 2006, Hrushesky et al 2011, we observe no positive correlation between sunspot and mortality rates in our study. The cyclical and dynamic interaction of space-weather components driven by solar activity can affect human health and behavior, possibly by inducing unexpected episodes of higher oxidative stress, to which humans have to constantly adapt to live on Earth.…”
Section: Discussioncontrasting
confidence: 99%
“…In contradiction to some studies that have described the association of high solar activity and human health in the literature (Palmer et al 2006, Hrushesky et al 2011, we observe no positive correlation between sunspot and mortality rates in our study. The cyclical and dynamic interaction of space-weather components driven by solar activity can affect human health and behavior, possibly by inducing unexpected episodes of higher oxidative stress, to which humans have to constantly adapt to live on Earth.…”
Section: Discussioncontrasting
confidence: 99%
“…4 highlights this phase of rising regional temperatures, and the start of the strong solar cycles that in later years (Since the 1970s), started showing substantial coupling with strong El Niño episodes. Figure 3a and d also shows mass balance periodicities of 9–12 years during ~1970–1990, a representation of the response to a few of the strongest consecutive solar cycles in past 400 years 53 . In fact, we see that ~50% of the years since 1970 experienced an exceptionally high TSI of >1361 Wm −2 , ~40% of which also underwent warm phases of ENSO.…”
Section: Comparisons and Recent Trendsmentioning
confidence: 99%
“…Correlations have also been reported between solar cycles and longevity [34], although such findings remain equivocal [35]. A further series of studies have revealed associations between the solar cycle and flu pandemics [36], and a similar relationship was recently reported with papillomavirus infections [37]. Relationships have also been observed between GMA and sudden infant death syndrome [38] and epilepsy [39].…”
Section: Introduction (A) Geomagnetic Navigation In Animalsmentioning
confidence: 80%